THE ROLE OF FUNCTIONAL FRUITS AND VEGETABLES ON HEALTH - nFN Siswanto (GIZI INDONESIA, 2014)
In the last three decades, there has been an evolution of nutrition science from classical nutrition science covering macro and micro nutrients into current nutrition science that elaborate not only basic nutrients (macro and micro nutrients) but also functional foods and omic science of nutrition (nutrigenomics and nutrigenetics). There are 7 categories of bioactive compounds in fruits and vegetables considered as functional foods, i.e. carotenoids, dietary fibre, fatty acids, phenolics (flavonoids), plant sterols, prebiotics/probiotics, and soy phytoestrogens. One category of functional foods which is believed to be important for degenerative disease prevention is phenolic compounds, considered as antioxidants. In principle, antioxidants will neutralise free radicals (radical oxygen species and radical nitrogen species) by donating their electron. Free radical is believed to cause inflammation and destruction of cell structure which in turn would cause the occurrence of degenerative diseases. Therefore, antioxidants are claimed as physiologically active compounds that can prevent a number of degenerative diseases, like cancer, cardiovascular disease, cataract, macular degeneration, chronic lung diseases, immune deficiency diseases, Diabetes Melitus, in facts, HIV/AIDS.ABSTRAKPERAN BUAH DAN SAYUR FUNGSIONAL TERHADAP KESEHATAN Dalam tiga dekade terakhir terjadi evolusi pada perkembangan ilmu Gizi, dari ilmu gizi klasik yang mencakup gizi makro dan mikro ke arah ilmu gizi masa kini yang menggali tidak saja ilmu gizi dasar tetapi juga pangan fungsional dan ilmu Omic dalam Gizi. (nutrigenomic dan nutrigenetik). Terdapat 7 jenis komponen bioaktif dalam buah dan sayuran yang disebut pangan fungsional, seperti karotenoid, serat, asam lemak, phenol (flavonoids), sterol dari tanaman, prebiotik dan probiotik, dan kedelai phytoestrogens. Satu jenis pangan fungsional yang dipercaya sangat penting dalam mencegah penyakit degenerative adalah senyawa phenol, termasuk dalam golongan antioksidan. Prinsipnya, antioksidan akan menetralisir radikal bebas(radical oxygen species dan radical nitrogen species) dengan memeberikan elektronnya. Radikal bebeas dipercaya dapat menyebabkan inflamasi dan penghancuran struktur sel yang pada akhirnya akan menyebabkan terjadinya penyakit degeneratif. Karena itu, oksidan diakui sebagai senyawa aktif secara physiologik yang dapat mencegah sejumlah penyakit degeneratif, seperti kanker, penyakit jantung dan pembuluh darah, katarak, degenerasi makular, penyakit kronis paru, penyakit kekurangan imun, kencing manis, dan termasuk HIV/AIDS.Kata kunci: pangan fungsional, senyawa bioaktif, penyakit degeneratif